TIJAUAN YURIDIS ATAS PELAKSANAAN PEMILU LEGISLATIF TAHUN 2014 DI PROVINSI KEPULAUAN RIAU - Shahrullah, Rina Shahriyani; Wagiman, Wagiman; Topan, Rendra (Journal of Judicial Review, 2013)
The abstract in this article is available in printed form.